ANALISIS PEMBELAJARAN MATEMATIKA BERDASARKAN KURIKULUM 2013 PADA SMA NEGERI 1 MASOHI - Ratumanan, Tanwey Gerson; Tetelepta, Yosep (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
This study aims to analyze the ability of mathematics teachers in planning and implementing learning as a form of the 2013 curriculum implementation. The study was conducted at SMA Negeri 1 Masohi, involving 3 mathematics teachers. The teachers are from of class X (M1), XI (M2), and XII (M3). Data was collected using assessment and review of the learning implementation plan prepared by each teacher, and conducting an assessment of the teaching and learning process managed by the three mathematics teachers. The instruments used consisted of two assessment formats, namely RPP assessment format, and learning assessment format, using a scale of 0 - 4. The results shows average quality the third RPP of teachers is 67.01 and included in the sufficient category (C) and the teacher has not been able to carry out learning as a form of implementation of the 2013 curriculum well. The average score of the ability to carry out learning is 66.33 and is included in the sufficient category (C), and teachers have not been able to carry out a structured, planned, and good assessment. They does not compile assessment instruments, both for the assessment of knowledge, as well as evaluating attitudes and skills. Assessment of student attitudes is carried out by teachers in general through observation of class activities and group activities without using assessment instruments